Investigating the effects of metabolic dysregulation on hair follicles: a comparison of HIV‐infected women with and without central lipohypertrophy. (20th June 2013) - Mirmirani, Paradi; Maurer, Toby; Cohen, Mardge; D'Souza, Gypsymber; Karim, Roksana; Plankey, Michael; Robison, Esther; Sharma, Anjali; Tien, Phyllis C.; Hessol, Nancy A.
Abstract Background Normal lipid metabolism and functioning of the peroxisome proliferator‐activated receptor gamma (PPAR‐gamma) in the sebaceous gland is critical to maintaining a normal hair follicle. Human immunodeficiency virus (HIV) infection affects lipid metabolism; some have hypothesized a link between PPAR‐gamma function and lipodystrophy in HIV infection. Our objective was to determine whether lipodystrophy is associated with altered hair characteristics in HIV‐infected women from the Women's Interagency HIV Study. Methods Hair characteristics and scalp inflammation were assessed by an interviewer‐administered questionnaire. Central lipohypertrophy and peripheral lipoatrophy were defined by self‐report of moderate to severe fat gain in central body sites and fat loss in peripheral body sites, respectively confirmed by clinical examination. Additional covariates considered in the analyses included demographics, behavioral characteristics, medical history, and HIV‐related factors. Results There were 1037 women with data on all study variables; 76 women reported central lipohypertrophy, while only four women reported lipoatrophy. Women with central lipohypertrophy were more likely to be older, had a self‐reported history of injection drug use, statin medication use, diabetes, elevated cholesterol, and have self‐reported less hair and shorter eyelashes. After adjustment for age, central lipohypertrophy was associated with shorter eyelashes (OR 2.3; 95% CI 1.4–3.8). Conclusions Central lipohypertrophy was not associated with change in scalp hair texture or scalp inflammation in this cohort. Rather, we found an association between central lipohypertrophy and shorter eyelash length. This finding may be explained by an influence of prostaglandin E2 mediators on eyelash follicles.